SOLID-STATE 29SI MAS NMR STUDIES OF ILLITE AND ILLITE-SMECTITE FROM SHALE - Lausen S.K.; Jakobsen H.J.; Nielsen N.C.; Lindgreen H. (My University, 1999)
A new method to extract quantitative information from poorly resolved 29 Si magic-angle spinning (MAS) nuclear magnetic resonance (NMR) spectra of natural mixed-layer illite-smectite (I-S) clays is presented. The Si-Al distribution in layered aluminosilicates are used to link the intensities of 29 Si resonances from all Q 3 (nAl) sites (n = 0, 1, 2, 3) to the tetrahedral layer aluminum substitution by applying Loewenstein's aluminum avoidance principle (no Al-O-Al linkages) extended to ensure a homogeneous distribution of charge. In addition, correlations between 29 Si chemical shifts and the A1 substitution are established for illite resonances by computer fitting of well-resolved phyllosilicate spectra. Combination of these two constraints led to a general procedure for iterative fitting of 29 Si MAS NMR spectra of clay minerals containing high-charge (illite-like) and low-charge (smectite-like) sites. The applicability of the new method is demonstrated for two I-S samples from Cambrian black shale in the Baltic area and two I-S samples from Upper Jurassic oil-source rock in the Central Trough of the North Sea. In combination with data from XRD and chemical analysis, the results from 29 Si MAS NMR enables determination of the composition for the entire I-S particles.
Keywords: Jurassic; Cambrian; Paleozoic::Cambrian; Mesozoic::Jurassic; Мезозой::Юрская; Палеозой::Кембрийская